Impact of rubber surface interactions on the morphology of clusters. Issue 3 (3rd July 2019) - Schneider, Gerald J.; Hengl, W.; Brandt, K.; Schuster, R.; Göritz, D.
ABSTRACT: We studied the influence of the adhesion strength of rubber chains and silica surfaces on the morphology of clusters by means of small-angle X-ray scattering experiments. We used mono- and bifunctional silanes and compare the results to untreated silica in different rubbers. We demonstrate a universal impact of the concentration on the cluster size and number of particles in agglomerates. The magnitude of the effects depends on the strength of the interactions between chains and particle surfaces. Best dispersion is obtained for bifunctional silanization.